1998
DOI: 10.1207/s15327752jpa7103_3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Malingering Posttraumatic Stress Disorder on the Personality Assessment Inventory

Abstract: Utilizing the Personality Assessment Inventory (PAI; Morey, 1991), this study aimed to isolate a pattern of responding that is indicative of an attempt to malinger posttraumatic stress disorder (PTSD). The PAI profiles of 116 male participants were examined. Profiles of a group of 29 alcohol-abusing veterans with a primary Axis I (American Psychiatric Association, 1994) diagnosis of PTSD and a group of 30 alcohol-abusing veterans with no other diagnoses were compared to those of 27 undergraduate men instructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…NIM and MI also performed well in three known group studies, but the RDF was completely ineffective in the one known group study that examined it (see Table 4). Guriel and Fremouw's (2003) review noted only two studies examining malingering PTSD on the PAI (Calhoun et al 2000;Liljequist et al 1998) and concluded that empirical data showed that the PAI's response-style indicators did not equal the discrimination of corresponding MMPI-2 scales. However, in both of these studies, the patient groups were veterans unscreened for possible feigning.…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 99%
“…NIM and MI also performed well in three known group studies, but the RDF was completely ineffective in the one known group study that examined it (see Table 4). Guriel and Fremouw's (2003) review noted only two studies examining malingering PTSD on the PAI (Calhoun et al 2000;Liljequist et al 1998) and concluded that empirical data showed that the PAI's response-style indicators did not equal the discrimination of corresponding MMPI-2 scales. However, in both of these studies, the patient groups were veterans unscreened for possible feigning.…”
Section: Self-report Inventories and Structured Interviewsmentioning
confidence: 99%
“…Liljequist et al (1998) compared PTSD symptomology among genuine PTSD sufferers (i.e., war veterans) and a student control sample that was instructed to malinger. They reported a trend where malingerers scored higher than veterans with PTSD on six different clinical scales assessed: depression, schizophrenia, anxiety, somatic complaints, paranoia, and antisocial features.…”
mentioning
confidence: 99%
“…Nevertheless, in their review of the measure, Sellbom and Bagby (2008) noted strong support for the use of the PAI validity indicators in assessing response bias, based on research employing both known-groups and simulation designs (see Bagby, Nicholson, Bacchiochi, Ryder, & Bury, 2002, Baity, Siefert, Chambers, & Blais, 2007Boccaccini, Murrie, & Duncan, 2006;Edens, Poythress, & Watkins-Clay, 2007;Kucharski, Toomey, Fila, & Duncan, 2007;Liljequist, Kinder, & Shinka, 1998;Morey & Lanier, 1998).…”
Section: Personality Assessment Inventorymentioning
confidence: 99%